Tools for a systematic appraisal of integrated community-based approaches to prevent childhood obesity - K. Mantziki; C. M. Renders; M. J. Westerman; J. Mayer; J. M. Borys; J. C. Seidell (BMC, 2018)
Abstract Background Evaluation and monitoring methods are often unable to identify crucial elements of success or failure of integrated community-wide approaches aiming to tackle childhood overweight and obesity, yet difficult to determine in complex programmes. Therefore, we aimed to systematically appraise strengths and weaknesses of such programmes and to assess the usefulness of the appraisal tools used. Methods To identify strengths and weaknesses of the integrated community-based approaches two tools were used: the Good Practice Appraisal tool for obesity prevention programmes, projects, initiatives and intervention (GPAT), a self-administered questionnaire developed by the WHO; and the OPEN tool, a structured list of questions based on the EPODE theory, to assist face-to-face interviews with the principle programme coordinators. The strengths and weaknesses of these tools were assessed with regard to practicalities, quality of acquired data and the appraisal process, criteria and scoring. Results Several strengths and weaknesses were identified in all the assessed integrated community-based approaches, different for each of them. The GPAT provided information mostly on intervention elements whereas through the OPEN tool information on both the programme and intervention levels were acquired. Conclusion Large variability between integrated community-wide approaches preventing childhood obesity in the European region was identified and therefore each of them has different needs. Both tools used in combination seem to facilitate comprehensive assessment of integrated community-wide approaches in a systematic manner, which is rarely conducted. Nonetheless, the tools should be improved in line to their limitations as recommended in this manuscript.